2017
DOI: 10.1080/10888438.2017.1283694
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Span in Oral Reading: The Case of Chinese

Abstract: The present study explores the perceptual span, that is, the physical extent of the area from which useful visual information is obtained during a single fixation, during oral reading of Chinese sentences. Characters outside a window of legible text were replaced by visually similar characters. Results show that the influence of window size on the perceptual span was consistent across different fixation and oculomotor measures. To maintain normal reading behavior when reading aloud, it was necessary to have in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…During sentence reading, the effective area of vision (i.e., the perceptual span; McConkie and Rayner, ) extends beyond the currently fixated word/character. In Chinese, the span extends one character to the left and up to three or four characters to the right of the current fixation (Inhoff and Liu, ; Pan, Yan, and Laubrock, ; Yan, Zhou, Shu, and Kliegl, ), indicating that reading involves extraction of information not only from the fixated words in the fovea but also from the upcoming words in the parafovea. While traditional behavioural studies have revealed basic cognitive mechanisms of single foveal word reading, the eye movement recording in naturalistic sentence reading can examine the early processing of the upcoming parafoveal word.…”
Section: The Error Disruption Paradigmmentioning
confidence: 99%
“…During sentence reading, the effective area of vision (i.e., the perceptual span; McConkie and Rayner, ) extends beyond the currently fixated word/character. In Chinese, the span extends one character to the left and up to three or four characters to the right of the current fixation (Inhoff and Liu, ; Pan, Yan, and Laubrock, ; Yan, Zhou, Shu, and Kliegl, ), indicating that reading involves extraction of information not only from the fixated words in the fovea but also from the upcoming words in the parafovea. While traditional behavioural studies have revealed basic cognitive mechanisms of single foveal word reading, the eye movement recording in naturalistic sentence reading can examine the early processing of the upcoming parafoveal word.…”
Section: The Error Disruption Paradigmmentioning
confidence: 99%
“…During oral reading, articulatory constraints on the oculomotor system may limit pre-saccadic attentional shifts to parafoveal words (Pollatsek et al, 2006;Rolfs et al, 2011). This view is compatible with reduced capacity for parafoveal processing in oral reading compared to silent reading within lines (Ashby et al, 2012;Inhoff & Radach, 2014;Pan et al, 2017). Because, line boundaries are also influenced by this kind of processing, readers may foveate closer to the left and right margins to process the letters there.…”
Section: Discussionmentioning
confidence: 95%
“…There is a palpable effect of parafoveal semantic information in reading Chinese, and there is more preponderance of parafoveal processing in Chinese than in alphabetic scripts (Bai et al, 2009;Sommer et al, 2014;Li et al, 2015;Liu et al, 2016;Zhang et al, 2019). Although parafoveal processing efficiency reduces in oral reading than silent reading (Ashby et al, 2012;Inhoff & Radach 2014;Pan et al, 2017), I assume that when reading danmu comments, viewers tend to read without articulating the texts, due to presence of the sound of videos, so the preview benefit is less likely to be impaired. That is to say, Chinese danmu can be processed more expeditiously than alphabetic scripts, and thus its unique success in China.…”
Section: Prerequisites For the Popularity Of Danmumentioning
confidence: 99%